A systemic approach to achieving population‐level impact in injury and violence prevention. (14th January 2020) - Smith, L. Shakiyla; Wilkins, Natalie J.; McClure, Roderick J.
Abstract: The contemporary public health model for injury and violence prevention is a four‐step process, which has been difficult to fully actualize in real‐world contexts. This difficulty results from challenges in bridging science to practice and developing and applying population‐level approaches. Prevention programmes and policies are embedded within and impacted by a range of system‐level factors, which must be considered and actively managed when addressing complex public health challenges involving multiple sectors and stakeholders. To address these concerns, a systemic approach to population‐level injury and violence prevention is being developed and explored by the Division of Analysis, Research, and Practice Integration in the National Center for Injury Prevention and Control at the Centers for Disease Control and Prevention. This article makes the case for and provides a high‐level overview of this systemic approach, its various components, and how it is being applied in one governmental unit.